Peran dan Tugas Administrator Food dan Beverage Service pada Oakwood Hotel dan Residence - Clara Geovani Rain; Dewi Khrisna Sawitri (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this study was to determine the role and duties of the food & beverage service administrator at oakwood hotel & residence. Food and Beverage Service is the second largest source of revenue for hotel operations after room sales. The purpose of this study is to determine the duties and responsibilities of the food and beverage service administrator at Oakwood Hotel & Residence Surabaya, establish standard operating procedures for food and beverage service at Oakwood Hotel & Residence Surabaya, and find ways to improve service quality. There are several obstacles in food and beverage service, such as detailed information obtained from businesses that are still difficult to implement due to incomplete information and lack of good communication between the sales department and the food service department. The research method used in this report is qualitative method by conducting observation through direct observation at Oakwood Hotel & Residence and library method. The implications of this research include: Oakwood Hotel & Residence must prepare a food and beverage service administrator and the food and beverage department must have good relationships and cooperation with other departments, such as the accounting department and purchasing department. This can be achieved by holding staff meetings to foster a sense of connectedness and encourage communication.